Online monitoring of autocorrelated multivariate linear profiles via multivariate mixed models. Issue 3 (4th May 2022) - Khalili, Somayeh; Noorossana, Rassoul
ABSTRACT: Multivariate multiple profile monitoring has been studied extensively over the past few years. Most of these studies assumed that the observations are uncorrelated, which could be violated in practice. In this paper, multivariate linear mixed model is proposed to allow correlation among observations of the multivariate multiple linear profiles. In order to monitor random effects and process variability in phase II, three control charts are suggested. The results of performance comparisons with an existing method show the superiority of the proposed control chart. Finally, the applicability of the proposed method is illustrated using a real case.